การวิเคราะห์ต้นทุนการให้บริการผู้ป่วยประกันสังคมในปีงบประมาณ 2541 โรงพยาบาลจุฬาลงกรณ์ - จุฑามาศ โมฬี (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
Finds unit cost of social security patients Service in the Fiscal year 1998 at King Chulalongkorn Memorial Hospital from perpective of providers. The study collected data by using retrospective surveys (1 October 1997-30 September 1998). Cost centre will be classified into three categories: Non Revenue-Producing Cost Centre, Revenue-Producing Cost Centre and Patient Service, which allocated by Simultaneous Equation Method. Total cost will be calculated from labor cost, material cost and capital cost. Capital cost is calculated by sensitivity analysis. Cost of drug, cost of medical supply, cost of laboratory and cost of X-Ray are calculated by Cost-Charge ratio. The study revealed that total cost of social security patients service in the Fiscal year 1998 consist of Out-Patient and In-Patient Departments are 34,783,106.05 baht and 30,345,226.61 baht respectively. Unit cost of social security out-patient services is 641.80 baht per visit and 389.80 baht per registered per year. Considering component parts ofunit cost, medical care cost are 471.73 baht per visit and 286.51 baht per registered person per year respectively. The routine service cost is 107.07 baht per visit and 103.29 baht per registered person per year. Unit cost of social security in-patient services is 2,678.07 baht per patient day and 340.07 baht per registered person per year. Considering component parts of unit cost, medical care cost are 1,684.84 baht per patient day and 213.95 baht per registered person per year. Unit cost of routine service is 848.33 baht per patient day and 107.72 baht per registered person per year respectively. The unit cost of social security patients service of hospital is 729.87 baht per registered per year compares to average capitation is 956.00 baht per registered per year, Thus unit cost of social security patients services is lower than average capitation (226.13 baht per registered per year). Out-patient social security services and in-patient social security services Utilization are 0.61 per registered per year and 0.02 per registered per year respectively. This study provides the basic information for the administrators of hospital in order to plan and control for social security patients Services expenditure efficiently and determines guidelines to decrease unit cost of social security patients services